Consideraciones para el diseño de las redes principales de extinción de incendio (2015)
In the civil and hydraulic engineering is the discipline of fire protection. In Colombia, this discipline is booming with the demands of national regulations, the application of international regulations and the creation of the General Law of Firefighters of Colombia. This degree project is aimed at people with engineering and architecture profiles who work in the field of design and construction of buildings. This document proposes a methodology to define the regulations that must be applied in an existing or new construction in the city of Bogotá and the design of a main fire extinguishing network is carried out. The methodology and design were implemented by the general fire fighting networks of the Colombian School of Engineering, using the hydraulic conditions established in national and international regulations.